The relationship of cardiorespiratory fitness, birth weight and parental BMI on adolescents’ obesity status - Vale, Susana (2010)
The aims of this study were as follows: (1) to analyze differences in cardiorespiratory fitness (CRF), parents' body mass index (BMI) and birth weight (BW) between non-overweight (NOW) and overweight/obese (OV/OB) adolescents, and (2) to investigate the association of those variables with the risk of their biological offspring being OV/OB. This study comprised 788 adolescents (477 girls and 311 boys), aged between 12 and 18 years. CRF was predicted by maximal multistage 20-m shuttle-run test according to the procedures described in FITNESSGRAM. Children's BMI was classified according to the International Obesity Task Force. Adolescents' BW was assessed from each child's pediatric record at birth. Parents' OV/OB status was defined and classified according to the World Health Organization. Socioeconomic status was defined by parental education. The prevalence OV/OB was 21.4 and 5.3%, respectively, and there were no gender differences. The OV/OB adolescents (girls and boys) had significantly (P<or=0.05) lower CRF scores and higher BW (P<or=0.05) than did the NOW pears. Overall, 92.9% of OV/OB girls had one or two parents with OV/OB (P<or=0.05). Boys with low CRF (odds ratio (OR): 3.75; P<or=0.05) and high BW (OR: 1.65; P<or=0.05) were more likely to be classified as OV/OB compared with NOW. Girls with low CRF (OR: 2.66; P<or=0.05), high BW (OR: 2.09; P<or=0.05) and at least one parent (OR: 2.28; P<or=0.05) or two parents with OV/OB (OR: 4.39; P<or=0.05, respectively) were classified as OV/OB. Results from this study highlight the association between the family adolescents' obesity, in girls. Furthermore, our data suggested that low CRF and high BW were strong predictors of OV/OB in adolescence.